The epidemiology of corticosteroid-induced osteoporosis: a meta-analysis. - van Staa, T; Leufkens, H; Cooper, C (2002)
Studies of oral corticosteroid dose and loss of bone mineral density have reported inconsistent results. In this meta-analysis, we used information from 66 papers on bone density and 23 papers on fractures to examine the effects of oral corticosteroids on bone mineral density and risk of fracture. Strong correlations were found between cumulative dose and loss of bone mineral density and between daily dose and risk of fracture. The risk of fracture was found to increase rapidly after the start of oral corticosteroid therapy (within 3 to 6 months) and decrease after stopping therapy. The risk remained independent of underlying disease, age and gender. We conclude that oral corticosteroid treatment using more than 5 mg (of prednisolone or equivalent) daily leads to a reduction in bone mineral density and a rapid increase in the risk of fracture during the treatment period. Early use of preventive measures against corticosteroid-induced osteoporosis is recommended.